Knowledge Management Implementation to Improve Branch Key Performance (Case Study in Sharia Bank of XYZ Branch) - Qadratullah, M. Wifaq; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2015)
Abstract.The purpose â€“ this research is focusing on the formulation of the appropriate KM program which can be used and implemented by the branch on its daily branch operation in order to improve branch key performance with the case study in Sharia Bank of XYZ Branch.Business Issue â€“ the declining of branch key performance in the year of of 2013 compared to the previous years, and this condition urgently need to be noticed by the management as well as overall staff, so the performances on the following years will be better.Design/methodology/approach â€“ the methods which is used in this research is quantitative research, with using the Descriptive Statistic method to collect data and present it in the form of tables, diagrams, etc. The data collection approaches in this research are through: 1. Interview process to the branch management in order to gain broader perspective and to find out the main cause of the research problem. 2. The questionnaire process to all employees in the branch and itâ€™s used as a tool to collect and record information related with the current and expectation condition of knowledge management implementation in the Sharia Bank of XYZ branch.Findings â€“ the research found that by analyzing the branch current condition of KM implementation for variable of people, process and technology, branch is still lacking in the critical dimension on each variables which were contributed to the declining of branch key performance. The appropriate KM formulation were produced in this research (by using â€œthe Five Steps Knowledge Management Implementationâ€ concept from Garfield), in accordance with the branch conditions with the KM Objectives emphasizing on the increasing of KM awareness, employee competencies and branch knowledge sharing.Keywords â€“ Islamic banking, Sharia Branch, KPI, KM Program, KM Implementation. Â Â